Komodifikasi Agama dalam Perspektif Hadis: Analisis Kritis dengan Teori Konstruksi Sosial - Muhammad Salim Mangunsong; Ibnu Hajar Ansori; Mohammad Fajar Alchusyairi (Prodi Ilmu Hadis Fakultas Ushuluddin dan Dakwah Universitas Islam Negeri Madura, 2025)
The commodification of religion is a contemporary social phenomenon characterized by the transformation of religion from a source of transcendental values into a commodity governed by market logic, manifested through religious businesses, the exploitation of religious symbols, and the expansion of the spiritual industry. This phenomenon poses a serious challenge in Islam, as it risks undermining the principle of sincerity (ikhlÄá¹£) and distorting the true purpose of worship. This study aims to examine Prophetic hadith perspectives on religious commodification, with particular attention to hadiths emphasizing sincerity and warnings against worldly orientation in religious practices. The research employs a library-based qualitative method using a descriptive-analytical approach, combined with thematic (mawá¸Å«â€˜Ä«) analysis of relevant hadiths, supported by classical scholarly commentaries (shurÅ«á¸¥ al-á¸¥adÄ«th). To contextualize the analysis, this study integrates Peter L. Bergerâ€™s theory of religious objectification, which explains how sacred religious values may be reduced to social constructions subject to economic rationality. The findings reveal that religious commodification has the potential to erode spiritual integrity, obscure the ultimate objectives of worship, and weaken the moral foundations of the Muslim community. Hadiths on ikhlÄá¹£ firmly assert that religious acts must be directed solely toward Allah, free from economic motives or social recognition. Meanwhile, Bergerâ€™s theoretical framework elucidates the social mechanisms through which religion may lose its sacred function when instrumentalized. In conclusion, a contextual and critical understanding of hadith is essential to preserving the authenticity of Islamic values in the face of religious commodification within contemporary social dynamics.